CSF in Epileptic Prodromal Alzheimer's Disease: No Diagnostic Contribution but a Pathophysiological One - Cretin, Benjamin; Bousiges, Olivier; Hautecloque, Geoffroy; Philippi, Nathalie; Blanc, Frederic; Dibitonto, Laure; Martin-Hunyadi, Catherine; Sellal, François (Frontiers in Neurology, 2021)
Objective: To study whether cerebrospinal fluid (CSF) analysis may serve as a diagnostic test for the screening of epilepsy in sporadic prodromal Alzheimer’s disease (AD). Methods: A total of 29 patients with epileptic prodromal sporadic AD patients (epADs) were included and were retrospectively compared with 38 non-epileptic prodromal AD patients (nepADs) for demographics, clinical features, Mini-Mental Status Examination (MMSE) results, CSF biomarkers, and electro-radiological features. Results: Our study did not show any significant differences in CSF biomarkers regarding neurodegeneration, albumin levels, and inflammation between epADs and nepADs. The epADs were significantly older at diagnosis (p = 0.001), more hypertensive (p = 0.01), and displayed larger white matter hyperintensities on brain magnetic resonance imaging (MRI; p = 0.05). There was a significant correlation between the CSF Aβ-42 and Aβ-40 levels with interictal epileptiform discharges and delta slowing on EEGs recordings, respectively (p = 0.03). Conclusions: Our study suggests that CSF may not serve as a surrogate marker of epilepsy in prodromal AD and cannot circumvent the operator-dependent and time-consuming interpretation of EEG recordings. In humans, AD-related epileptogenesis appears to involve the Aβ peptides but likely also additional non-amyloid factors such as small-vessel disease (i.e., white matter hyperintensities).